An Iranian familial amyotrophic lateral sclerosis pedigree with p.Val48Phe causing mutation in SOD1: a genetic and clinical report - Alavi, Afagh (Iran J Basic Med Sci, 2014)
OBJECTIVE(S): Amyotrophic lateral sclerosis (ALS), a fatal progressive neurodegenerative disorder, is the most common motor neuron disease in European populations. Approximately 10% of ALS cases are familial (FALS) and the other patients are considered as sporadic ALS (SALS). Among many ALS causing genes that have been identified, mutations in SOD1 and C9orf72 are the most common genetic causes of the disease. In Iranian patients, it has been shown that SOD1, as compared to C9orf72, plays a much more prominent role. To date, more than 170 mutations have been reported in SOD1. Genotype/phenotype correlation with respect to either different causative genes or different mutations of a specific gene has not been well established. MATERIALS AND METHODS: Five exons of SOD1 and flanking intronic sequences of an Iranian FALS proband were screened for mutations by direct sequencing. Also, the clinical features of the proband were described. RESULTS: Heterozygous p.Val48Phe causing mutation was identified in SOD1. Age at onset was 29 years and site of the first presentation was the lower extremity in the proband. CONCLUSION: The p.Val48Phe causing mutation appears to cause early onset of ALS.